Buckwheat: A Cool-Season Cover Crop for Florida Vegetable Systems - Danielle D. Treadwell; Pei-wen Huang (EDIS)
HS-1135, a 7-page illustrated fact-sheet by Danielle Treadwell and Pei-wen Huang, describes this “pseudocereal” commonly grown as a cover crop in the southeast, growth habits, environmental requirements, role as a nutrient catch crop, interactions with insects, potential for weed control and weed suppression, and economics. Includes references. Published by UF Department of Horticultural Sciences, February 2008.